The Relationship Between Infant Birth and Perineal Rupter in Normal Delivery in Juwita Clinic - Novi Susanti; Sri Ilawati (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
The number of perineal rupture cases continues to increase each year. Birth weight is a risk factor that increases the incidence of perineal injury. The bigger the baby born the risk of perineal rupture. The coverage rate for participants for mothers who gave birth at the Juwita Midwife Clinic in 2022 recorded 14 participants, 9 women who had normal births experienced tears in the birth canal. The purpose of this study was to determine the relationship between birth weight and perineal rupture in normal delivery at the Juwita Midwife Clinic in 2022. This research is an analytical study with a cross-sectional research design. This research was conducted at the Juwita Midwife Clinic, Hamparan Perak, Deli Serdang Regency, North Sumatra Province. The time of the study was in May-July 2022. The population in the study was all maternity patients at the Juwita Midwife Clinic who gave birth in May-July 2022 as many as 55 normal birth mothers. The sampling technique used in this research is non-probability sampling with total sampling technique. The number of samples in this research was 55 people. Collecting data in this study used a questionnaire in the form of a check list sheet. Univariate analysis with descriptive, while bivariate analysis with Chi-Square test. The results of the research were that mothers experienced perineal rupture by giving birth to normal baby weight ≤4000 grams, namely 17 mothers (30,9%) of whom gave birth with babies weighing more than 4000 grams, namely 18 mothers (32,8%). There is a relationship between birth weight and perineal rupture at the Juwita midwife clinic, Hamparan Perak District, Deli Serdang Regency (p-value=0,040). It is recommended that health workers can increase their vigilance in providing birth assistance so that perineal rupture does not occur.Keyword: Maternity, Newborn Weight, Perineal Rupture